1981
DOI: 10.1001/archotol.1981.00790450049016
|View full text |Cite
|
Sign up to set email alerts
|

Cartilaginous Metaplasia of Soft Tissues in the Larynx: Case Report and Literature Review

Abstract: MB, BS, FRCPA, Pal V. Rajagopalan, MB, BS, DLO, MS \s=b\ Cartilaginous metaplasia in the larynx is distinguished from true cartilaginous neoplasms by the occurrence of fibroblast-like cells at the periphery of islands of cartilage and a progressive transition of these cells to chondrocytes toward the center. Also present in the transitional zone was diffuse intercellular stromal acid mucopolysaccharide and dense aggregates of elastin fibers. The importance of distinguishing these metaplastic lesions from tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

1983
1983
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 2 publications
0
7
0
Order By: Relevance
“…In the larynx, a frequent example of epi thelial change is the squamous metaplasia of pseudostratified columnar epithelium, while the osseous metaplasia is common in old age. There are only a few reports on chondromatous metaplasia in the human larynx [1,2], although the lesion is not rare [1], This case is an example of cartilaginous metaplasia in the vestibular fold of the larynx.…”
Section: Discussionmentioning
confidence: 93%
“…In the larynx, a frequent example of epi thelial change is the squamous metaplasia of pseudostratified columnar epithelium, while the osseous metaplasia is common in old age. There are only a few reports on chondromatous metaplasia in the human larynx [1,2], although the lesion is not rare [1], This case is an example of cartilaginous metaplasia in the vestibular fold of the larynx.…”
Section: Discussionmentioning
confidence: 93%
“…Laryngeal chondrometaplasia is not uncommon in postmortem study and is found in 1 - 2% of examined larynges ( 1 ). However, it is usually small in size (usually less than 1 cm in diameter) and thus asymptomatic ( 1 ). Symptomatic laryngeal chondrometaplasia is rare and seldom reported ( 2 , 3 ).…”
Section: Discussionmentioning
confidence: 99%
“…There are only a few reports on laryngeal chondrometaplasia in the literature, although a postmortem study revealed that microscopic foci of metaplastic cartilage may be found in about 1-2% of all examined larynges. [1][2][3] This discrepancy derives from the fact that such lesions are usually small (usually less than 1 cm in diameter) 1 4 and asymptomatic, so that surgical treatment is rarely needed. Laryngeal chondrometaplasia shows a predilection for the posterior and midportions of the glottis, and for the ventricular bands.…”
Section: Discussionmentioning
confidence: 99%